BUILDING RESILIENT HEALTH SYSTEMS: THE CRITICAL ROLE OF PRIMARY HEALTH CARE AND NATIONAL HEALTH INSURANCE - Ernawaty (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2024)
This editorial article explores the critical role of primary health care (PHC) in building resilient health systems, particularly within the context of Indonesia's National Health Insurance (JKN) program. It emphasizes the importance of universal access to comprehensive health services as a fundamental aspect of effective PHC. The discussion highlights best practices for strengthening PHC, including enhancing collaboration between public and private sectors, improving information exchange, and establishing quality evaluation systems. The article also addresses significant challenges, such as workforce shortages and coordination issues between primary and secondary health services. Furthermore, it underscores the necessity of developing suitable assessment tools, such as the Primary Care Assessment Tool (PCAT), to evaluate and enhance PHC services tailored to local needs. The findings suggest that addressing poverty is essential for improving access to health care, requiring collaborative efforts across various societal sectors. Overall, the article advocates for sustained investment in PHC to achieve better health outcomes and resilience in health systems. Keywords: Health Insurance, Health System, Primary Health Care